A Framework Proposal for Detecting and Preventing Academic Misconduct in Japanese Language as L2 - Ozsen, Tolga; Cente-Akkan, Senem (Canadian Perspectives on Academic Integrity, 2021)
Japanese is a language in which its sociocultural background affects strongly the acquisition and output processes for the L2 learners. The acquisition process has more layers not only because it has 4 unique ideogram-based writing system (Hiragana, Katakana, Kanji and Romaji), but also has differences in writing procedures (e.g., orthographic rules, punctuation marks, etc.). The interaction in daily life with Japanese language and culture is extremely limited, particularly for the Japanese L2 learners who are outside of the Kanji cultural zone. Those kinds of factors make the academic misconduct issues in Japanese language learning/writing process more complicated. On the other side, academic misconduct issues (detection techniques, tools, prevention methods, etc.) in the Japanese language are mostly considered within the framework based on Western languages. However, as it is mentioned earlier, Japanese language has fundamental differences in linguistic, communicative, cultural, historical aspects. In a language where there is no double quotation mark as it is in Western languages, even punctuation marks are unique, and 4 different writing systems are used together, academic misconduct issues can be partially detected and prevented with a framework based on Western languages. Therefore, it is necessary to establish a framework for specific foreign languages as Japanese to detect and prevent from academic misconduct. This paper aims to offer a research framework to be made later about academic misconduct that targets Japanese L2 learners and receive feedback about the experiences in different disciplines and languages to develop the research framework and tools. As we will only present the framework of the survey, this presentation will not promise concrete research findings. The survey we are planning to conduct will be composed of three sections. First section will aim to reveal the cognitive/notional knowledge of Japanese L2 learners on academic misconduct such as plagiarism, cheating. Second section will try to find out what motivations led Japanese L2 learners to academic misconduct. In the third section, Japanese L2 learners' procedural knowledge on academic misconduct will be evaluated by giving learners various Japanese texts.